Peningkatan Literasi dan Numerasi untuk Siswa SD Negeri Dermo 2 dengan Menggunakan Media Video Interaktif (Proceedings of The National Conference on Community Engagement, 2026)
Literacy and numeracy skills are fundamental competencies that must be mastered by elementary school students. The low literacy and numeracy achievement rates among students require the development of learning innovations that are engaging, contextual, and aligned with students’ developmental characteristics. The study aims to determine whether interactive video media influence the literacy and numeracy skills of elementary school students. A one-group pretest–posttest design was used in this study. The subject of the study was a student of Dermo 2 State Elementary School. All research subjects were administered a pretest, after the intervention was given, all students were directed to fill out the posttest sheet to give the results of the intervention. This study uses literacy and numeracy test instruments based on the Minimum Competency Assessment (AKM) indicators. Statistical tests and the Paired Sample t-Test are used to analyze the research data. The average pretest score of 57.87 increased drastically to 83.67 in the posttest. A significance value of 0.000 (